Dampak penerapan GSG dimediasi reputasi sekolah terhadap kinerja SMK Swasta di Kota Malang - Anak Agung Rai Susilawathi; Umi Muawanah; Ahmad Ahmad (Jurnal Ekonomi Modernisasi, 2021)
Vocational Education is a level of education that develops students' abilities to carry out certain types of work. Vocational High Schools have many expertise programs that adapt to the needs of the existing world of work. Good School Governance (GSG) is very much needed in improving school performance, especially vocational high schools in order to be able to improve school quality. The research objectives were to analyze the effect of GSG on school reputation, to analyze the effect of GSG on school performance, to analyze the effect of school reputation on school performance. This research is a quantitative study that describes the impact of the implementation of GSG mediated by the reputation of the school on the performance of private vocational high schools in Malang. The data used are primary data from 43 private vocational high schools in Malang. The sampling technique used non-probability sampling techniques, namely saturated sampling, with the principal respondents of private vocational high schools in Malang City. Data were analyzed using Path Analysis. The results showed that GSG had a significant effect on school reputation, GSG had a significant effect on school performance, school reputation had a significant effect on school performance, GSG had a significant effect on school performance mediated by school reputation.